THE PERFECT BEING OF R. M. P. SOSROKARTONO'S THINKING - Tafrichul Fuady Absa (UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. This article reviews R. M. P. Sosrokartono's thoughts about the perfect human being. He defines a perfect being as a person who is able to live up to the knowledge of ngawoelo dateng kawoelaning Goesti. In order to have such life and behavior that reflect the attributes of God by loving and maintaining the wholeness of God's creation, therefore, the alignment must be based on catur murti. That is, to be able to unite and balance feelings, thoughts, words, and actions. The union of the four components is based on the value of truth so that the actualization in life becomes the proper thought, feeling, word, and action. That is the perfect being who will become caliph on earth. Abstrak. Artikel ini mengulas pemikiran R. M. P. Sosrokartono tentang manusia paripurna. Baginya, manusia paripurna adalah manusia yang mampu menghayati ilmu ngawoelo dateng kawoelaning Goesti. Sehingga hidup dan perilakunya akan mencerminkan sifat-sifat Tuhan dengan cara mencintai dan menjaga keutuhan ciptaan Tuhan. Penyelarasan itu harus didasari oleh catur murti. Yaitu, mampu menyatukan sekaligus menyeimbangkan antara perasaan, pikiran, perkataan, dan perbuatan. Penyatuan empat komponen tersebut berdasarkan pada nilai kebenaran, sehingga penyatuan itu menjadi pikiran yang benar, perasaan yang benar, perkataan yang benar dan perbuatan yang benar. Itulah manusia paripurna yang menjadi khalifah di muka bumi.